Fosfito de potássio no controle de Colletotrichum gloeosporioides, isolado de plantas de cafeeiro com sintomas de mancha manteigosa - Ogoshi, Cláudio (2011)
The present study was aimed to evaluate the effect of potassium phosphite on germination, appressorium formation and mycelial growth of Colletotrichum gloeosporioides;check the control of the pathogen in vivo, study the mechanisms involved in the defense response in coffee seedlings and analyze the events of germination and penetration of the pathogen by scanning electron microscopy. Four experiments were conducted. The treatments were: doses of potassium phosphite 1,25 mL L-1; 2,5 mL L-1; 5,0 mL L-1 and 10,0 mL L-1; Acibenzolar-S-Metil 0,1g L-1 and water sterile. The doses 5.0 mL L-1 and 10.0 mL L-1 of potassium phosphite stood out in reducing the percentage of germinated conidia, inhibition of appressorium formation and in reducing the rate of speed of mycelial growth of pathogen. The dose of potassium phosphite 10.0 mL L-1 reduced the area under the curve of progress of disease severity by 62.5% standing out from the other treatments. This treatment without inoculation increased peroxidase activity 1 day after spraying, 6 days after spraying of polyphenoloxidase and 3 days after spraying of chitinase. When inoculated, did not induce increase of peroxidase activity, but at 13 days after spraying there was a peak of formation of the enzymes polyphenoloxidase and chitinase. All treatments failed to induce increased β-1, 3 glucanase activity. Conidial germination, observed by scanning electron microscopy, it started four hours after inoculation of the pathogen, with a maximum formation after 12 hours, where initiated the formation of appressoria. Penetration occurred most often mechanically and 16 hours after inoculation, was observed hyphae of the pathogen within the plant tissues. This study showed that potassium phosphite is a promising product in the control of Colletotrichum gloeosporioides in coffee, but for this product will become a technological innovation for the farmers need more field studies.